Analysis of The Relationship Between Warranty and Returns on Consumer Loyalty at Car Dealership in the Application of Conditional Khiyar - Manurung, Nabila Tasya Nurhafifah; Nasution, Juliana; Syarbaini, Ahmad Muhaisin B. (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This research aims to analyze the relationship between the warranty policy and return policy implemented by the Medan Daihatsu Car Dealer and the level of consumer loyalty, especially in the application of the Conditional khiyar principle in business transactions. The research method used was a quantitative approach using a questionnaire as a data collection instrument, the number of samples used was 60 respondents. The data analysis technique uses multiple linear regression analysis and the hypothesis tests are the t test, F test and coefficient of determination which are processed with SPSS 25 Version software. The collected data will be analyzed using statistical techniques such as regression to assess the relationship between the variables studied. Apart from that, this research can also be a reference for further research in the field of marketing management and business law related to the implementation of conditional khiyar in business transactions.